Exposure to Copper Compromises the Maturational Competency of Porcine Oocytes by Impairing Mitochondrial Function - Chen, Jingyue; Cui, Zhaokang; Qiu, Yawei; Zhang, Xingxing; Chen, Fang; Wang, Huili; Xiong, Bo; Miao, Yilong; Gao, Qian (Frontiers in Cell and Developmental Biology, 2021)
Copper (Cu) is an essential trace element for animals, and also an important nutritional component for the normal physiology and metabolism of animal reproductive systems. An excess or lack of Cu will directly or indirectly affect animal reproductive activities. However, the effect of Cu, in particular excessive Cu, on the reproductive performance of sows has not been studied. Here, we report that excessive Cu had negative effects on oocyte maturation and organelle functions. We showed that Cu exposure perturbed porcine oocyte meiotic maturation and impaired spindle/chromosome structure, resulting in defective spindle assembly, as well as abnormal distribution of actin dynamics and cortical granules. In addition, single-cell transcriptome analysis identified target effectors of Cu actions in porcine oocytes, further demonstrating that Cu exposure affects the mitochondria distribution and function, leading to the high levels of reactive oxygen species, DNA damage, and early apoptosis of porcine oocytes. These findings demonstrate that Cu exposure causes abnormalities in mitochondrial distribution and function, resulting in increased oxidative stress and levels of reactive oxygen species, DNA damage and apoptosis, ultimately leading to decreased porcine oocyte quality.